2020
DOI: 10.1177/0956462419881074
|View full text |Cite
|
Sign up to set email alerts
|

Delays in HIV and TB diagnosis and treatment initiation in co-infected patients in Colombia

Abstract: We investigated the delays in the diagnosis of tuberculosis and/or HIV, their treatment initiation, and factors associated with each delay. All drug-susceptible tuberculosis cases diagnosed in 2014 and 2015 in Colombia, with a confirmed diagnosis of HIV were included. A total of 1909 patients were registered with tuberculosis/HIV co-infection. Seventy-nine percent of patients were men, 50% had sputum smear-negative tuberculosis, culture was done in 50% of cases, 68.5% had <200 CD4 cell count at diagnosis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(48 reference statements)
1
2
0
Order By: Relevance
“…We also show that the risk of HIV/EBV-1/2 multiple infection was higher in patients with longer HIV-1 infection, which emphasizes our warning because coinfections are common in patients who start treatment late, have the highest associated risk rate, and are also correlated with advanced clinical disease stages 117 , 118 . For EBV, this becomes more specific because the prevalence of EBV-1 and of multiple infection predominate in the most immunosuppressed patients; however, it is not known which factors may be involved in this scenario 44 , 119 .…”
Section: Discussionsupporting
confidence: 56%
“…We also show that the risk of HIV/EBV-1/2 multiple infection was higher in patients with longer HIV-1 infection, which emphasizes our warning because coinfections are common in patients who start treatment late, have the highest associated risk rate, and are also correlated with advanced clinical disease stages 117 , 118 . For EBV, this becomes more specific because the prevalence of EBV-1 and of multiple infection predominate in the most immunosuppressed patients; however, it is not known which factors may be involved in this scenario 44 , 119 .…”
Section: Discussionsupporting
confidence: 56%
“…In a South African cohort including only PLWH with pulmonary TB older age (> 40 years) and HIV-RNA viral load > 400 copies/ml were predictors for delayed diagnosis, while being on ART at time of diagnosis was associated with lower risk of delayed diagnosis [ 20 ]. A study including all drug-susceptible TB cases in PLWH from Colombia found age between 15–34, age ≥ 45 years, and receiving tuberculin skin tests as a part of the diagnostic work-up associated with delayed diagnosis [ 21 ]. In a Brazilian cohort of 242 PLWH with TB, factors associated with patient delay were the symptoms asthenia, chest pain, and the use of illicit drugs, including IDU [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An estimated 38.0 million people were living with HIV/AIDS globally with the annual number of deaths standing at 970,000 in 2021, and 25% were co-infected with Mycobacterium tuberculosis ( M.tb ), the causative agent of TB [ 1 ]. Albeit that there are diagnostic tests currently available for HIV and TB, the diagnosis of these two diseases is still performed separately and this can delay treatment in co-infected individuals, particularly because active TB diagnosis can take a long time [ 2 , 3 ]. With HIV, there is a rapid test for the detection of p24, in addition to the PCR test.…”
Section: Introductionmentioning
confidence: 99%